Delignification of untreated elephant grass (EG) using microwave assisted bleaching process prior to nano-cellulose crystal isolation: effect of hydrogen peroxide concentration on lignin degradation: article / Fathin Nor Faridah Mohamed Nawi - Mohamed Nawi, Fathin Nor Faridah; Abd Rahman, Norazah; Mohd Zuki, Syaidatul Akma (2019)
Nanocrystal cellulose isolation involved pretreatment stages which are alkali pretreatment and bleaching. Nevertheless, those pretreatment are using conventional method and do not give a significant results in lignin degradation. Microwave assisted process for nanocrystal cellulose isolation expected to be efficient in the lignin degradation. The objectives are to extract cellulose from untreated elephant grass using microwave assisted bleaching process and determine lignin degradation using different concentration of hydrogen peroxide (H2O2) as bleaching agent. Untreated elephant grass will be bleached using different concentration of hydrogen peroxide in different time. The percentage of total lignin degradation can be determined from the summation of acid soluble lignin (ASL) and acid insoluble lignin (AIL). The result showed that the highest weight of biomass after bleaching process is 1.6301g meanwhile for percentage of total lignin degradation is 49.93% at 120 minutes, 30% concentration of H2O2 with 180W. This can be conclude that microwave assisted bleaching process can be an effective pretreatment method for nanocrystal cellulose isolation.